Effects of learning style on students achievement: experimental research - Ha, Nguyen Thi Thu (Linguistics and Culture Review, 2021)
This study aims at investigating the relationship between learning styles and academic achievement in Physics of high school students in Thai Nguyen city, Vietnam. In this study, we selected a simple random sample consisting of students attending high schools located in Thai Nguyen city (Luong Ngoc Quyen High School, Iron Steel High School, Thai Nguyen High School; Duong Tu Minh High School; Ngo Quyen High School; Luong the Vinh High School; Dao Duy Tu High School) from 2019-2020; 2020-2021. This study used the formula for sample size calculation developed by Watson (2001), our population size is 307 students. This study used an online questionnaire survey method using Google form and Zalo form. Survey was conducted from April 2019 to May 2021. The result implied that different learning styles accompanied with learning setting can contribute greatly to students’ academic achievement.